(untitled) (Global Journal of Management and Business Research, 2013)
This paper reports on findings from a research project that reflected upon the effectiveness of the undergraduate dissertation process of Final-year HND students in the Takoradi Polytechnic Business Programs. The research adopted a quantitative methodology and gathered the perspectives of students involved in the HND undergraduate dissertation process. Questionnaires were used to collect the data, which were assessed against the research outcomes that were reviewed. The outcomes of the reflection provide a reference for ongoing dissertation with the aim to ensure an effective HND undergraduate dissertation process or abolishing of dissertation as part of partial fulfillment for the HND Certificate for Business Undergraduate Students. The study surveyed 500 students and reviewed 100 dissertations of Business students in the dissertation module. Descriptive statistics were used for the survey and review. The findings revealed that the HND dissertation is ineffective because it lacks the quality standard of an undergraduate dissertation.